(untitled) (Revista de Crítica Literaria Latinoamericana, 2017)
This paper analyzes the symbolic matrix of the North-American political discourse developed by José Vasconcelos in his essay La raza cósmica (1925). Vasconcelos’ essay contains a paradox: The semiotic and ideological constant incidence of the North-American political discourse in his own thesis on Latinamericanism and anti-North-americanism—these thesis are summarized in Vasconcelos’ concepts of misión [Mission] and destino manifiesto [Manifest Destiny]. The aproppiation of this North-American Rethoric is determined by two reasons: on one hand, Vasconcelos’ subaltern experience; on the other hand, Vasconcelos’ strategy to get political support from the North-American community. This paradox could be explained by the notion of enunciation—as developed by E. Benveniste and re-developed under the paradigm of Post-Colonial Studies. According to my reading, in Vasconcelos’ essay, under the North-American rethoric, there are two underlying motivations: Vasconcelos’ symbolic Split, and the “significant double intention” of his politic enunciation.